US-China economic rivalry and the reshoring of global supply chains - Gür, Nurullah; Dilek, Şerif (Oxford University Press, 2023)
Since the Global Financial Crisis (GFC) of 2008, the USA has changed its economic priorities and policy preferences in a concerted effort to bolster its weight in the global economy, reduce over-reliance on global supply chains, and create more employment within its borders. This change has become more apparent in the wake of the Trump presidency and the COVID-19 pandemic. Reviving the manufacturing industry through reshoring is now the main goal of US politicians. This article analyses the two strategies, in light of heightened technological competition with China, that the USA has brought into effect to reshore its factories from the People's Republic of China and so revitalise the American manufacturing industry. They are neo-protectionism and smart automation. Arguing that neo-protectionist policies and smart automation technologies are interrelated factors that have been used strategically to bring American multinational companies in China back to the USA, we examine whether or not these two strategies-each elements of the US-China tech war-can support the reshoring and revitalisation of the American manufacturing industry. We find that increased neo-protectionist measures and proliferation of smart automation technologies alone will not empower the USA sufficiently to consolidate its technological superiority over China, add impetus to its manufacturing investments, and create well-paying jobs for the broader segments of American society through the reshoring of manufacturing activities. To achieve these goals, the USA should instead implement an integrated policy framework that spans industrial policies to technology policies and tax policies to labour market policies. Otherwise, even though reshoring may gain a certain momentum, new industrial facilities will not expand productivity enough to raise the competitiveness of the US economy to satisfactory levels, and such investments might not provide enough new job opportunities to remediate socioeconomic problems.
Keywords: Global Supply Chains; US-China; Economic Rivalry